The Erosion of selected tungsten coatings by ion beam and plasma sources compared to calculated predictions - Jackson, Mike; Bunting, Patrick; Lee, Vivian; Vishnyakov, Vladimir; Bradley, James W; Ali, Zeyad; Thornley, Sarah; Dutson, James; Cox, David; Zhuk, Yuri; Wagenaars, Erik (Fusion engineering and design, 2023)
•Erosion of tungsten samples was measured in ion beams and low temperature plasmas.•Sputter yield code was written and compared to experiment.•Developed code results give reasonable results and are quick calculations.•Erosion rate of several tungsten coatings were compared to each other. Tungsten is proposed as a tokamak divertor armour due to its good erosion resistance. Combining tungsten coatings with copper as a base material can overcome problems with machinability, lower the weight and reduce the component cost. The erosion rate must be known to estimate the lifetime of plasma facing components. This work aims to compare selected tungsten coatings to check if the erosion rate remains as good. It also compares the experimental data to a developed code based on previous work that aims to be quick and simple while giving reasonable results. In this study a set of erosion experiments were undertaken to measure the sputter yield in different conditions at partner organisations; Helium ion beam erosion at Huddersfield University, Helium plasma erosion at the University of Liverpool, Argon plasma erosion at Plasma Quest Ltd and Xenon Focussed Ion Beam (FIB) erosion at University of Surrey This work compares sputter yields different tungsten samples: sheet material, Chemical Vapour Deposition tungsten coating, Additive Manufacture deposited tungsten and tungsten coatings laid down by Thermal Plasma Spray. These coatings are available commercially so are ready to deploy today. The experimental sputter yields were compared to theoretical predictions, based on previously published work. While the experimental results agreed well with the models in trend and angular dependence the quantitative agreement was only well predicted to within a factor of four. It was found that the coatings have similar, and sometimes slightly lower sputter yields, and therefore, on occasion, slightly better erosion performance than the stock tungsten sheet samples.